1995
DOI: 10.1017/s0025315400039023
|View full text |Cite
|
Sign up to set email alerts
|

Is a mollusc an evolved bent metatrochophore? A histochemical investigation of neurogenesis in Mytilus (Mollusca: Bivalvia)

Abstract: Acetylcholinesterase (AChE) activity, a marker of neural differentiation, was histo-chemically localized in embryos and larvae of Mytilus galloprovincialis Lamarck and M. edulis L. (Mollusca: Bivalvia). The results show that: (1) the first AChE-active cells develop as two bilaterally symmetrical, postero-dorsal pioneer sensory neurons and their supporting superficial cells; (2) the pathways of their pioneering longitudinal axons are the same as those of two bilaterally symmetrical nerve cords which differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
3

Year Published

1999
1999
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 27 publications
4
24
3
Order By: Relevance
“…Velar innervation had been thought to originate from the cerebral ganglia (Arkett et al 1987;Carter 1926Carter , 1928Mackie et al 1976), but more recently it has been shown that axons may actually emerge from cells of the apical organ in some of the Opisthobranchia (Kempf et al 1997;Marois and Carew 1997a-c) and I. obsoleta (Prosobranchia; see Lin and Leise 1996a, b). In addition, velar innervation has also been reported from cells that may comprise an apical organ in M. edulis (Bivalvia; see Croll et al 1997;Kulakovskiy and Flyachinskaya 1994;Raineri 1995;Raineri and Ospovat 1994). Although the origin of velar innervation could not be determined in C. fornicata from this present study, it is likely that such extensive innervation arises from the apical cells since fibers were observed in velar regions prior to the first cells of the cerebral or pedal ganglia.…”
Section: Innervation Of the Velummentioning
confidence: 53%
See 2 more Smart Citations
“…Velar innervation had been thought to originate from the cerebral ganglia (Arkett et al 1987;Carter 1926Carter , 1928Mackie et al 1976), but more recently it has been shown that axons may actually emerge from cells of the apical organ in some of the Opisthobranchia (Kempf et al 1997;Marois and Carew 1997a-c) and I. obsoleta (Prosobranchia; see Lin and Leise 1996a, b). In addition, velar innervation has also been reported from cells that may comprise an apical organ in M. edulis (Bivalvia; see Croll et al 1997;Kulakovskiy and Flyachinskaya 1994;Raineri 1995;Raineri and Ospovat 1994). Although the origin of velar innervation could not be determined in C. fornicata from this present study, it is likely that such extensive innervation arises from the apical cells since fibers were observed in velar regions prior to the first cells of the cerebral or pedal ganglia.…”
Section: Innervation Of the Velummentioning
confidence: 53%
“…An apical organ has been reported in some of the Gastropoda (Bonar 1977(Bonar , 1978Chia and Koss 1984;Kempf et al 1991Kempf et al , 1997Lin and Leise 1996a, b;Marois and Carew 1997c;Moor 1983;Page 1993;Raineri 1995;Raineri and Ospovat 1994) and the Bivalvia (Raineri 1995;Raineri and Ospovat 1994) as well as many other swimming invertebrate larvae (see for example, Hay- Schmidt 1990a-c, 1995Lacalli 1981Lacalli , 1994. In many molluscs (Bonar 1978;Chia and Koss 1984;Kempf et al 1997;Leise 1996;Marois and Carew 1997a, b) and other invertebrates (see Lacalli 1994), the apical organ possesses flask-or vase-shaped cells with protruding cilia at the epithelial surface.…”
Section: Apical Organmentioning
confidence: 98%
See 1 more Smart Citation
“…The few studies that have focused on bivalves to date have examined only restricted developmental stages and/or employed histochemical staining techniques with limited resolution and questionable speciWcity (Ospovat et al 1989;Koolakovsky and Phlyachinskaya 1993;Raineri and Ospovat 1994;Raineri 1995). Although 5-HT-containing neuronal elements have been observed in the apical region of the bivalves Mytilus edulis (Linn茅 1758) (Croll et al 1997;Flyachinskaya 2000) and Spisula solidissima (Dillwyn 1817) (Kreiling et al 2001), the exact locations of these cells in the larval apical organ versus the cerebral ganglia are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, bivalves are generally considered more closely related phylogenetically to gastropods than to polyplacophorans (see Taylor 1996), while on the other hand, the nervous system of the trochophore of M. edulis has been suggested to closely resemble that of a larval annelid (Raineri 1995;Nielsen 2001). The anatomy of the adult annelid nervous system, however, more closely resembles (at least superWcially) that of polyplacophorans, rather than bivalves (Bullock and Horridge 1965;Beklemishev 1969).…”
Section: Introductionmentioning
confidence: 99%